2021
DOI: 10.26434/chemrxiv.13012814.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gausemycins A,B – Cyclic Lipoglycopeptides from Streptomyces Sp.

Abstract: We report a novel family of natural lipoglycopeptides produced by <i>Streptomyces</i> sp. INA-Ac-5812. Two major components of the mixture, named gausemycins A and B, were isolated, and their structures were elucidated. The com-pounds are cyclic peptides with a unique peptide core and several remarkable structural features, including unusual posi-tions of D-amino acids, lack of the Ca<sup>2+</sup>-binding Asp-X-Asp-Gly (DXDG) motif, tyrosine glycosylation with arabinose, presence of 2-a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We have taken daptomycin and ramoplanin to compare the features of the gausemycin A resistance formation against two antibiotics which having certain similarities with gausemycin A. Earlier, we showed that gausemycin А has a mode of action similar to that of membrane-active lipopeptide daptomycin [19], while structurally more resemble lipoglycopeptide ramoplanin [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have taken daptomycin and ramoplanin to compare the features of the gausemycin A resistance formation against two antibiotics which having certain similarities with gausemycin A. Earlier, we showed that gausemycin А has a mode of action similar to that of membrane-active lipopeptide daptomycin [19], while structurally more resemble lipoglycopeptide ramoplanin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the new lipoglycopeptides were revealed among metabolites of actinomycete Streptomyces roseoflavus INA-Ac-5812. These lipoglycopeptides were first described in 2016 [17] and then were named as gausemycins A and B [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless and remarkably, O-glycosylation of Tyr is observed in several of these, namely in mannopeptimycins γ/d/ε 22 and in the gausemycins. 18 This decoration is also present in the fungal glycopeptide cycloaspeptide F 35 and in cacaoidin, 36 a recently described ribosomallysynthesized and post-translationally modified (RiPP) glycopeptide.…”
Section: Ms-guided Isolation Of Desmamides A-c (1-3)mentioning
confidence: 93%
“…This designation has been used to encompass both glycosylated lipopeptides and acylated glycopeptides. 17,18 Natural lipoglycopeptides are rare and are grouped in a small number of structural classes: the cyanobacterial hassallidins/balticidins, 19,20 the actinobacterial teicoplanin/teichomycins, 21 mannopeptimycins (γ, d and ε), 22 ramoplanins 23 and gausemycins, 18 as well as occidiofungins produced by a Gram-negative Burkholderia strain. 24 Potent antibacterial or antifungal activities are associated with each of these compound classes; teicoplanin and related semisynthetic lipoglycopeptides are used in the clinic to treat serious infections caused by Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%